Post-intubation tracheal lacerations: Risk-stratification and treatment protocol according to morphological classification - Cardillo, Giuseppe; Ricciardi, Sara; Forcione, Anna Rita; Carbone, Luigi; Carleo, Francesco; Di Martino, Marco; Jaus, Massimo O.; Perdichizzi, Salvatore; Scarci, Marco; Ricci, Alberto; Dello Iacono, Raffaele; Lucantoni, Gabriele; et al. (Frontiers in Surgery, 2022)
Background: Post-intubation tracheal laceration (PITL) is a rare condition (0.005% of intubations). The treatment of choice has traditionally been surgical repair. Following our first report in 2010 of treatment protocol tailored to a risk-stratified morphological classification there is now clear evidence that conservative therapy represents the gold standard in the majority of patients. In this paper we aim to validate our risk-stratified treatment protocol through the largest ever reported series of patients. Methods: This retrospective analysis is based on a prospectively collected series (2003-2020) of 62 patients with PITL, staged and treated according to our revised morphological classification. Results: Fifty-five patients with Level I (#8), II (#36) and IIIA (#11) PITL were successfully treated conservatively. Six patients with Level IIIB injury and 1 patient with Level IV underwent a surgical repair of the trachea. No mortality was reported. Bronchoscopy confirmed complete healing in all patients by day 30. Statistical analysis showed age only to be a risk factor for PITL severity. Conclusions: Our previously proposed risk-stratified morphological classification has been validated as the major tool for defining the type of treatment in PITL.